Ingestive behavior of steers on pastures of Brachiaria brizantha and Cynodon dactylon - Zanine, Anderson de M.; Vieira, Bruno R. [UNESP]; Ferreira, Daniele de J.; Vieira, Antonio J. M.; Silveira, Marcia C. T. da; Siva, Wilton L. da; Cecon, Paulo R. (Pontificia Univ Catolica Chile, Fac Agronomia Ingenieria Forestal, 2016)
An experiment was carried out to assess the performance of steers on Brachiaria brizantha and Cynodon dactylon cv. Coast cross pastures by the continuous stocking method with a variable stocking rate. A completely randomized experimental design was used with two pastures representing the treatments, each containing 10 replicates. The results of t-tests demonstrated that the steers grazed for less time (7:19 h) on the B. brizantha grass pasture than the on Coast-cross grass pasture (8:13 h). There was no difference in rumination time from 6:46 and 6:89 h for the B. brizantha and Coast-cross pastures, respectively. There was a significant difference for the values regarding the time that the steers remained idle, and the animals were more frequently idle on the B. brizantha pasture, which was associated with less grazing time because there was no significant difference in the total rumination time. The lowest bite rates were observed in the Coast-cross pasture compared with B. brizantha during the daytime and nighttime. Nonetheless, the total number of bites were significantly higher in the Coast cross pasture; however, the lowest bite rate overall was recorded in the B. brizantha pasture. These results suggested that there was a compensation mechanism between the grazing times and the bite rates so that the animals could regulate the quantity of forage ingested.
Keywords: cattle; ethology; grazing; idleness